Aid, Policies, and Growth: Reply - Burnside, Craig; Dollar, David (American Economic Review, 2004)
In Burnside and Dollar (2000) we used standard regression techniques from the growth literature to measure the effect of foreign aid on growth. The main finding in our paper was that the effect of foreign aid on growth depended on the macroeconomic policies of recipient countries. In this issue, William Easterly et al. (2004), challenge the robustness of our result to new data. Before commenting on their findings it is useful to review the basis of our original findings. Our paper focused on three versions of a panel growth regression, estimated using data for 51 countries, and six four-year periods, from 1970 to 1993. These regressions may be summarized as: